Post-ERP pancreatitis as a model for cytokine induced acute phase response in acute pancreatitis. Issue 1 (January 1997) - Messmann, H; Vogt, W; Holstege, A; Lock, G; Heinisch, A; von Fürstenberg, A; Leser, H G; Zirngibl, H; Schölmerich, J
Abstract : BACKGROUND/AIMS: By contrast with animal models, in most cases it is not possible to examine the systemic response in patients in the first hours after onset of acute pancreatitis. The aim was to determine whether endoscopic retrograde cholangiopancreaticography (ERP)-induced pancreatitis can be used as a human model for the study of cytokine release and acute phase response in the first hours of the disease. PATIENTS AND METHODS: Seventy consecutive patients undergoing ERP for different reasons were prospectively evaluated by sampling blood before and 0, 1, 4, 12, 24, and 48 hours after ERP and, in patients who developed an acute post-ERP pancreatitis, daily until C reactive protein (CRP) was within normal range. A post-ERP pancreatitis was defined as a three-fold increase of amylase or lipase and at least two of the clinical symptoms: abdominal pain, nausea, vomiting, and peritonism during 24 hours after ERP. RESULTS: Nine out of 70 patients developed an acute pancreatitis. Cytokines and other biochemical variables were measured in those nine and in 34 patients out of the 61 not developing pancreatitis. In the nine patients amylase and lipase increased within the first hour after ERP with maximum values between four and 12 hours. Interleukin-6 increased to maximal concentrations after 24-48 hours and the highest CRP concentrations were found 72 hours after ERP. Tumour necrosis factor did not change. CONCLUSION: Post-ERP pancreatitis is an ideal model in which to examine the initial cytokine and acute phase response in the first hours after the initiation of the disease.